OP29 'While my thinking is clear': outcomes from a feasibility pilot of a multidisciplinary, step-wise pathway for ACP in family medicine. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Tan, A; Paterson, C; Bernacki, R; Urquhart, R; Barwich, D; Howard, M
Abstract : Background: Advance care planning (ACP) and goals of care (GCD) discussions with patients align with the tenets of patient-centred shared decision-making central to family medicine (FM). We sought to determine whether a multidisciplinary pathway is feasible in family medicine to enable effective ACP conversations. This pathway reorders Ariadne Lab's Serious Illness Conversation Guide (SICG) with a values clarification tool in a step-wise approach to ACP. Methods: Mixed-methods feasibility pilot study of pathway implementation in an urban FM clinic in Alberta, Canada. We recruited community-dwelling patients age 60 or older with indications of frailty (multi-morbidity, unplanned hospitalizations), and their surrogate decision-maker (SDM). An allied health professional initiated the ACP pathway, which preceded an appointment with the family physician (FP) to complete the SICG discussion. We conducted a survey of patients and SDMs, and a focus group with clinicians to evaluate feasibility, acceptability and perceived impact. Results: Nine patients, seven SDMs, and four clinicians participated in the pilot. All patients and SDMs rated the process as "very good" or "excellent". Eight patients and two SDMs reflected that discussing and documenting their preferences helped them feel more prepared for future illness, and that involving SDMs was essential. Clinicians found the pathway and SICG improved their skills and empowered them to facilitate these conversations more effectively. Conclusions: This pathway that adapts use of the SICG was acceptable and effective for all participants. The pathway fits well into FM as the trusting relationship between the patient and FP provides the foundation for these meaningful conversations.